Impact of the Pharmacy Practice Model Initiative on Clinical Pharmacy Specialist Practice. Issue 5 (27th April 2016) - Jacobi, Judith; Ray, Shaunta'; Danelich, Ilya; Dodds Ashley, Elizabeth; Eckel, Stephen; Guharoy, Roy; Militello, Michael; O'Donnell, Paul; Sam, Teena; Crist, Stephanie M.; Smidt, Danielle
Abstract : This paper describes the goals of the American Society of Health‐System Pharmacists' Pharmacy Practice Model Initiative (PPMI) and its recommendations for health‐system pharmacy practice transformation to meet future patient care needs and elevate the role of pharmacists as patient care providers. PPMI envisions a future in which pharmacists have greater responsibility for medication‐related outcomes and technicians assume greater responsibility for product‐related activities. Although the PPMI recommendations have elevated the level of practice in many settings, they also potentially affect existing clinical pharmacists, in general, and clinical pharmacy specialists, in particular. Moreover, although more consistent patient care can be achieved with an expanded team of pharmacist providers, the role of clinical pharmacy specialists must not be diminished, especially in the care of complex patients and populations. Specialist practitioners with advanced training and credentials must be available to model and train pharmacists in generalist positions, residents, and students. Indeed, specialist practitioners are often the innovators and practice leaders. Negotiation between hospitals and pharmacy schools is needed to ensure a continuing role for academic clinical pharmacists and their contributions as educators and researchers. Lessons can be applied from disciplines such as nursing and medicine, which have developed new models of care involving effective collaboration between generalists and specialists. Several different pharmacy practice models have been described to meet the PPMI goals, based on available personnel and local goals. Studies measuring the impact of these new practice models are needed.